2015
DOI: 10.1016/j.aoas.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Root anatomy of some species of Amaranthus (Amaranthaceae) and formation of successive cambia

Abstract: The root anatomy of 12 Amaranthus taxa (Amaranthaceae) was studied. The internal structures were evaluated as an anatomical character to clarify the taxonomic complexity in the genus. Transactions of young roots of the studied species showed no variations. While the old roots examination revealed differences in the products of the secondary thickening and their distribution, also differences in the anomalous cambium products were detected. Twelve characters with 26 character stats were used to generate anatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
0
8
0
1
Order By: Relevance
“…The secondary structures of roots and stems observed in G. marginata show an unusual or anomalous thickening of the vascular cylinder due to the high activity of supernumerary cambia, resulting specially in the formation of abundant reserve tissues. This anomalous thickening is a common phenomenon in the Amaranthaceae (Metcalfe and Chalk, 1950; Menezes et al, 1969; Grosso, 2007; El-Ghamery et al, 2015; Sá et al, 2016) and Chenopodiaceae (Metcalfe and Chalk, 1950; Krumbiegel, 1998). In G. albiflora , root secondary growth was also considered atypical (Jáuregui et al, 2014) as the authors showed that the successive rings are formed from a lateral meristem producing parenchyma outward, supernumerary cambia and parenchyma inward.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary structures of roots and stems observed in G. marginata show an unusual or anomalous thickening of the vascular cylinder due to the high activity of supernumerary cambia, resulting specially in the formation of abundant reserve tissues. This anomalous thickening is a common phenomenon in the Amaranthaceae (Metcalfe and Chalk, 1950; Menezes et al, 1969; Grosso, 2007; El-Ghamery et al, 2015; Sá et al, 2016) and Chenopodiaceae (Metcalfe and Chalk, 1950; Krumbiegel, 1998). In G. albiflora , root secondary growth was also considered atypical (Jáuregui et al, 2014) as the authors showed that the successive rings are formed from a lateral meristem producing parenchyma outward, supernumerary cambia and parenchyma inward.…”
Section: Discussionmentioning
confidence: 99%
“…(2001) studied pollen variations, Adhikary and Pratt (2015) analysed pollen and floral variations within various species, and El-Ghamery et al . (2015) studied the root anatomies of 12 Amaranthus taxa.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Segment at the transition zone had GC 1 assigned to the main stem with three smaller stems that were not present in the above segments. EVANS: GROWTH CENTERS IN STEMS Rajput et al 2012, Abd Elbar 2015, El-Ghamery et al 2015, Pace et al 2018, Myskow et al 2019. Schenk (1999) reviewed mechanisms and patterns of axis splits and described the ecological functions of clonal splits in desert shrubs.…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
“…Plants exhibit many anatomical anomalies during secondary growth (Duff and Nolan 1953, Newman 1956, Esau 1965, Dobbins 1971, Fahn 1974, Mauseth 1988, Schweingruber et al 2006, Mauseth 2014). Examples of anomalies resulting from secondary growth caused by abnormal cambia include the formation of successive cambia (Fahn and Zimmerman 1982, Terazas 1991, Carlquist 2007, Rajput et al 2012, Abd Elbar 2015, El-Ghamery et al 2015, Pace et al 2018, Myskow et al 2019, regenerating cambia (Steward et al 1958, Gautheret 1959, Wilson and Wilson 1961, differential production of secondary tissues (Dobbins 1971, Horak 1981, supernumerary cambia (Kirchoff and Fahn 1984), fasciations caused by unusual cambium development (Albertson et al 1983, Tang andKnap 1998), cresting growths of cactus stem terminals (Thornton 2007), unequal cambial activity (Ayensa andStern 1964, Jones andLord 1982), and wood eccentricities (Diettert 1938;Ferguson and Humphrey 1959;Ferguson 1964;Evans et al 2019;Scarinci et al 2017;Evans and Graney 2018;Evans 2021a, b). Anomalous cambia produce xylem and phloem cells, but may also produce a variety of cell types (Newman 1956, Dobbins 1971.…”
mentioning
confidence: 99%